Characterizing Mandibular Morphology in Robin Sequence-A 3D Statistical Shape Analysis - El Ghoul, Khalid; O' Sullivan, Eimear; Guntaka, Praveen Kumar; van Heesch, Gwen G; Joosten, Koen F M; Pullens, Bas; Khonsari, Roman H; Resnick, Cory M; van de Lande, Lara S; Wolvius, Eppo B (The Journal of craniofacial surgery, 2025)
Robin sequence (RS) is a congenital condition and constitutes the triad of micrognathia, glossoptosis, and upper airway obstruction. While micrognathia is a cardinal feature of RS, its assessment is largely subjective. The aim of the present study is to describe 3D mandibular morphology in patients with RS and age-related mandibular shape variation compared with an age-matched control group. 3D reconstructions of the mandible were obtained from CT-imaging of children with isolated (iRS) and nonisolated RS (niRS). Principal Component Analysis was used to describe variation in mandibular morphology. Partial Least Squares and multivariate analysis of variance (MANOVA) were used to compare shape differences between patients with RS and 1:1 age-matched control groups. A total of 84 patients with iRS and 48 with niRS were included with a mean age of 5.4±8.4 months versus 11.0±13.9 months ( P -value<0.001). For the iRS and niRS groups, the first principal component primarily constituted allometric shape variation, as a high correlation was noted with age in both groups (Spearman R=0.79). Compared with the control group, both the iRS and niRS mandibles displayed shorter condylar necks, shorter mandibular bodies, and less pronounced, more rounded symphyseal projection (MANOVA, P -value<0.001). For both groups, a persistent difference in age-related shape changes along the first shape variable compared with the age-matched control group is observed. Variation in mandibular morphology in patients with RS for the included age range is primarily due to allometric shape changes. Patients with RS have distinct mandibular morphology relative to age-matched controls. The differences observed in the comparison of age-related shape changes are suggestive of a persistent dysmorphology for patients with iRS and niRS. Future studies will explore the association of mandibular morphology with clinical parameters.